HUBUNGAN TINGKAT PENGETAHUAN SIKAP DAN PERILAKU DIE T TERHADAP ANGKA KEKAMBUHAN PADA PENDERITA ARTRITIS GOUT DI POLI PENYAKIT DALAM RSUD D R. H. BOB BAZAR SKM KALIANDA LAMPUNG SELATAN TAHUN 2016 - Eka Sylvia; Boby Suryawan; Riskinda Marcilia (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2019)
Background : Gout artritis is one of joints inflamation, marked with monosodium crystalaccumulation in body joints which the management is difficult because related with patient’s lifehabits.Objective : This research aim is to know the relationship between knowledge,attitute,andbehavior of diet with relapsing rate on gout artritis patiens in departement of internalmedicine dr.H. Bob Bazar, SKM Kalianda South Lampung year 2016Method : The method used in this study is an analytic survey with cross sectional approach and usedaccidental sampling. The population in this study was 37 patients. Data was collected using primarydata, while univariate and bivariate analysis were used to analyze the data, using chi-square test.Result : The test results with chi-square statistic there is strong relationship between knowledge(p=0,010), attitude (p=0,006), behavior of diet (p=0,000) with relapsing rate on gout artritispatiens in departement of internal medicine dr. H. Bob Bazar, SKM Kalianda south Lampungyear 2016.Conclusion : from the result, we can conclude that know the relationship betweenknowledge,attitute,and behavior of diet with relapsing rate on gout artritis patiens in departementof internalmedicine dr. H. Bob Bazar, SKM Kalianda South Lampung year 2016